Tinjauan Yuridis terhadap Penyalahgunaan Kegiatan Perbankan dalam Penghimpunan Dana Masyarakat oleh Koperasi: Studi Putusan Nomor 271/Pid.Sus/2018/PN.Pti - Rifqi, Muhammad Jazil (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2021)
The existence of irregularities in banking activities carried out by non-bank institutions, in addition to violating applicable norms also results in losses for many people when there is embezzlement of funds. The juridical study of this literature research reveals that the implementation of criminal acts against violations of banking authority which in the judge's decision imposes criminal sanctions on cooperative leaders in the form of imprisonment for eleven years and an additional punishment in the form of a fine of ten billion provided that if not paid is replaced by imprisonment for six months economic offenses The judge's verdict which is more than the crimes committed by the perpetrator in harming society can be justified as stated in article 46 of the banking law. Non-bank institutions in the form of cooperatives in collecting public funds must obtain permission from the Minister of Cooperatives whose storage and use of funds is limited to their members, but if they carry out their services not from their members, it violates article 16 of the banking law. In addition, Article 59 of the Criminal Code also emphasizes that the leadership or management of a corporation that has a legal entity who commits a criminal act must bear the sanctions decided by the judge.